Optimalisasi Pelaksanaan Pergantian Crew Kapal dan Kontrak Perjanjian Kerja Laut (PKL) PT. Multi Jaya Samudra Belawan (International Forum of Researchers and Lecturers, 2023)
The optimization of ship crew changes and Maritime Employment Agreement (MEA) contracts implementation is a crucial challenge in the shipping industry. This abstract details a holistic approach to understanding the constraints, optimization strategies, and impacts associated with crew changes and MEA implementation. The literature review highlights constraints such as uncertainty in policy changes, bureaucratic obstacles, and resistance to change. To address these constraints, optimization strategies involve technology integration, risk management, enhanced communication, transparency in MEA, and investment in training and development. The positive impacts of optimization include improved operational efficiency, crew welfare, company reputation, onboard safety, and harmonious relationships. These strategies are expected to provide guidance for shipping companies to overcome challenges and improve the implementation of crew changes and MEA, creating a more efficient, stable, and sustainable shipping industry.